2012
DOI: 10.1155/2012/153415
|View full text |Cite
|
Sign up to set email alerts
|

TRIM22: A Diverse and Dynamic Antiviral Protein

Abstract: The tripartite motif (TRIM) family of proteins is an evolutionarily ancient group of proteins with homologues identified in both invertebrate and vertebrate species. Human TRIM22 is one such protein that has a dynamic evolutionary history that includes gene expansion, gene loss, and strong signatures of positive selection. To date, TRIM22 has been shown to restrict the replication of a number of viruses, including encephalomyocarditis virus (EMCV), hepatitis B virus (HBV), and human immunodeficiency vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 63 publications
0
53
4
Order By: Relevance
“…19 When 293T or COS7 cells were transfected with human TRIM22 tagged with GFP, TRIM22 was localized in the cytoplasm. 19 . TRIM22 was colocalized with NS5A in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 When 293T or COS7 cells were transfected with human TRIM22 tagged with GFP, TRIM22 was localized in the cytoplasm. 19 . TRIM22 was colocalized with NS5A in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…19,22,23 Moreover, in the serum-starved U2OS cell line, TRIM22 was localized in both the nucleus and cytoplasm. 19,24,25 Gao and colleagues observed that TRIM22 was mainly localized in the nucleus of HepG2 cells when it suppresses HBV survival. 13 The discrepancy in localization compared to our present study may be due to the different cell lines we used (Huh-7 cell lines).…”
Section: Ifn-a-induced Trim22 Interrupts Hcv Replicationmentioning
confidence: 94%
“…However, TRIM E3 ligases are a heterogeneous group of proteins, and little is known about the contribution of specific members of this family to antiviral activity in vivo and the factors that may contribute to differential expression or effectiveness in blocking viral replication (15,36,37). We hypothesized that TRIM E3 ligases, as a component of the innate immune system, may play a significant role in blocking retroviral infection during the early phases of infection and in a remote anatomical site likely deficient in a robust adaptive immune system.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, many members of the TRIM family induced in response to IFNs are associated with innate immunity and antiviral defence 24. Among them, TRIM22, one of the closest paralogs of TRIM5α, displays antiretroviral activity similar to that of TRIM5α 25. Several studies have found that TRIM22 inhibits the transcription and replication of HIV through suppression of its long terminal repeat and disruption of the intracellular trafficking of the viral Gag protein 26 27.…”
Section: Introductionmentioning
confidence: 99%